2017
DOI: 10.1091/mbc.e16-05-0325
|View full text |Cite
|
Sign up to set email alerts
|

Centriole splitting caused by loss of the centrosomal linker protein C-NAP1 reduces centriolar satellite density and impedes centrosome amplification

Abstract: Knockout of the centriolar linker C-NAP1 increased centriole separation and dispersed centriolar satellites. Primary cilia formed normally, even though the ciliary rootlet was mislocalized, and mechanosensory ciliary signaling was intact. Reduced levels of centrosome amplification after DNA damage indicate the importance of centriole proximity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 62 publications
6
32
0
Order By: Relevance
“…This observation suggests a role for centrin 2 in satellite regulation, consistent with the previously described localization of centrin to satellites (Löffler et al, 2013;Prosser et al, 2009). Alterations in centriolar satellite density can affect centrosome duplication (Flanagan et al, 2017;Kodani et al, 2015;Löffler et al, 2013;Prosser et al, 2009). Therefore, we quantitated centrosome amplification after ionizing (IR) and ultraviolet (UV) irradiation, visualizing centrioles with the proximal end marker CEP135 (Ohta et al, 2002) and centrin 3, which is representative of a distinct family of centrins ( Fig.…”
Section: Analysis Of the Ef-hand Domains Of Centrin 2 In Centriolar Lsupporting
confidence: 88%
“…This observation suggests a role for centrin 2 in satellite regulation, consistent with the previously described localization of centrin to satellites (Löffler et al, 2013;Prosser et al, 2009). Alterations in centriolar satellite density can affect centrosome duplication (Flanagan et al, 2017;Kodani et al, 2015;Löffler et al, 2013;Prosser et al, 2009). Therefore, we quantitated centrosome amplification after ionizing (IR) and ultraviolet (UV) irradiation, visualizing centrioles with the proximal end marker CEP135 (Ohta et al, 2002) and centrin 3, which is representative of a distinct family of centrins ( Fig.…”
Section: Analysis Of the Ef-hand Domains Of Centrin 2 In Centriolar Lsupporting
confidence: 88%
“…Previous evidence has suggested that centriolar satellites are required for recruiting many key regulators of centriole duplication to the centrosome. Other possible mechanisms explaining centriolar satellite dispersion at the onset of mitosis include NEK2A kinase-dependent loss of C-NAP1 from the centrosome leading to reduced centriolar satellite density (64). There may be additional mechanisms of centriolar satellite dispersion in mitosis and reorganization in G 1 that remain to be elucidated, and this is an important area of future research.…”
Section: Plk4 Phosphorylates Cep131mentioning
confidence: 99%
“…These properties meet the criteria for a centrosome linker component regulated by Nek2 at the G2/M transition. Indeed, subsequent experiments have revealed that cells lacking Nek2 fail to remove C-Nap1 from centrosomes upon mitotic entry (Fletcher et al, 2004 ; Mardin et al, 2010 ), while loss of C-Nap1 by antibody microinjection, RNAi-mediated depletion, gene-editing or disease-associated truncating mutations all lead to unscheduled separation of centrosomes in interphase (Mayor et al, 2000 ; Bahe et al, 2005 ; Floriot et al, 2015 ; Panic et al, 2015 ; Flanagan et al, 2017 ).…”
Section: Nek Kinases In Centrosome Disjunctionmentioning
confidence: 99%